HOUSING QUALITY ASSESSMENT CRITERIA (Advances in Civil and Architectural Engineering, 2021)
An apartment is a basic need and a primary unit of human habitation, and in most cases, it represents the largest investment of someone’s life. For that reason, and because of constant changes in housing needs, it is necessary to continuously evaluate the housing quality of apartments. The aim of this paper is to provide an overview of the criteria used for housing quality assessments in existing studies. Due to the large number of defined criteria, four groups of criteria were established: apartment unit quality criteria, apartment building quality criteria, neighborhood quality criteria, and social and economic criteria. The defined criteria can be divided according to the different scales of the assessed spaces (apartment unit, building, and neighborhood), and according to the method of assessment (quantitative or qualitative). The trend suggests that the numbers of individual criteria and criteria groups have increased over time, and they have become more complex. Also, it can be concluded that the number of criteria related to adaptability and sustainability will increase and lead to even more complex criteria relations. The defined criteria can be used in future research and serve as a basis for the proposal of a set of highly valuable criteria for examining attitudes toward housing quality.